Evaluation of Meibomian Gland Dysfunction and Local Distribution of Meibomian Gland Atrophy by Non-contact Infrared Meibography. (3rd October 2015) - Finis, David; Ackermann, Philipp; Pischel, Nadja; König, Claudia; Hayajneh, Jasmin; Borrelli, Maria; Schrader, Stefan; Geerling, Gerd
Abstract: Aims : The main purpose of this study was to investigate the relationship between Meibomian gland atrophy (meiboscore) and Meibomian gland expressibility. In addition, the local distribution of Meibomian gland loss was analyzed. Methods : A retrospective analysis of 128 patients (92 women and 36 men, 57 ± 17 years) from our dry eye clinic was performed. Infrared meibography was performed using the Keratograph 5 M (Oculus, Wetzlar, Germany) and evaluated with a scoring system introduced by Arita et al. Results : A significant inverse correlation between Meibomian gland atrophy measured by meibography and expressible Meibomian glands ( r = −0.197, p = 0.003) as well as between meiboscore and TBUT ( r = −0.1615, p = 0.012) was found. There also was a significant correlation between the total meiboscore and the age ( r = 0.33, p < 0.0001). We could find a strong and highly significant correlation between the total meiboscore and the individual meiboscore of the upper eyelid ( r = 0.905, p < 0.0001) and the lower eyelid ( r = 0.892, p < 0.0001). There was no significant difference of Meibomian gland atrophy between the individual thirds of the upper eyelid, but for the lower eyelid, we could find a higher degree of Meibomian gland atrophy in the nasal third compared with the middle and the temporal third (Dunn's post hoc test, p < 0.0001). Conclusions : Meibomian gland atrophy seems to be not constant over the tarsal plate but the examination of the lower tarsus might be sufficient in most of the cases. The correlation of the meiboscore with functional dry eye parameters suggest that in patients with detectable Meibomian gland atrophy there is also an impaired Meibomian gland function. However, meibography seems not to be sufficient as a single test for the diagnosis of MGD. For the future larger, prospective studies are needed to confirm these results and further evaluate the potential of meibography in the diagnosis of MGD.